PUSAT PENGEMBANGAN KREATIVITAS KAUM MARJINAL DIKOTA GORONTALO DENGAN PENDEKATAN ARSITEKTUR BAHAVIOUR - Isbiantoro Dwi Subandri Ansik; Nurnaningsih Nico Abdul; Kalih Trumansyahjaya (JAMBURA Journal of Architecture, 2019)
Center for the creativity development for marginal group in Gorontalo City is the place for shelter from violence, and reinstanting the behavioural activity of marginal group, grow community awareness that the marginal group should be appreciated for them to have appropriate living and get rid of all negative activities addressed to them by equipping them with art skills. The objective of the study was to design creativity development center for the marginal community in Gorontalo City which can increase the creativity of the marginal group in arts, either musical arts and local culinary for the poor, homeless, and street children. The method used in this study is data compilation. In this process data collection was the design process and the data were collected through observation, reference from books and literature study, case the analysis process. The analysis would solve the problems investigated in this process then interpreted into the design pictures of pre-architectural design in the design on was the Center for the creativity development for the marginal group in Gorontalo city with Behavioural Architecture theme as the basic concept to be applied into the phase and the massive arrangement of the Center for Creativity Development for Marginal Group which can be well utilized based on its function.